By the Honorable Thomas Fitch, Esq ; governor of His Majesty's English colony of Connecticut ... A proclamation for a day of public fasting and prayer : ... Wednesday the seventeenth day of April next ... Given under my hand in Norwalk, the eleventh day of March ... 1765 (Printed by Timothy Green, printer to the colony of Connecticut, 1765)
March 11, 1765 broadside issued by Governor Thomas Fitch of Connecticut, proclaiming April 17th as a day of public fasting and prayer, in light of the poor harvest.